Fostering Creative Writing through Poetry in EFL Classroom - Andania, Ruqoyyah Amilia; Dewi, Rohmatul Fitriyah; Romadhoni, Mohammad; Yen, Ai-Chun (Acitya: Journal of Teaching and Education, 2024)
This study was conducted to examine how the ELT teacher implements creative writing through poetry in the ELT classroom during pandemic and to describe how the students express their emotions through tone of poetry in their creative writing. It is due to the existence of creative writing in language teaching and learning practice is significant to gaining students’ creativity and thinking. One of them is writing poetry. However, few literatures discussed on the method used by teachers through writing poems as well as the concern for emotion and tone embedded in students’ writing products. This study used qualitative descriptive with Indonesian EFL university students of the non-English department at an Islamic University in Indonesia as the participants. The result shows that teachers use student-centered methods to implement creative writing through poetry in the classroom during the global COVID-19 pandemic. The meeting was organized using Zoom Meeting with performing Warm-Up, Lead-In (Creation of Poem and Reading the Poem), and Follow-up. In addition, it was also found that the student’s creative works posted on Instagram were based on the negative variations of poetry tone including threatening, painful, and discouraged. The study underscores the pedagogical efficacy of student-centered creative writing in ELT, highlighting its role in enhancing emotional intelligence and validating the integration of digital platforms for remote learning. It advocates for culturally responsive curricula that leverage creative expression as a conduit for emotional articulation and critical thinking